The use of modified-release methylphenidate in the treatment of attention-deficit/hyperactivity disorder. (1st February 2017) - Childress, Ann; Belchenko, Dmitry; Lempa, Brian
ABSTRACT: Introduction : Since Ritalin® (Methylphenidate-Immediate release or MPH-IR) was introduced for the treatment of attention-deficit/hyperactivity disorder, multiple formulations of MPH have been developed. The specific formulation determines the pharmacokinetic (PK) profile and the onset and duration of action for the compound. Areas covered : Aptensio XR® is a multilayer-release MPH (MPH-MLR) consisting of an MPH-IR layer (40%) and an extended-release (ER) portion of 60% of MPH. It has an initial maximum MPH concentration at about two hours (h) and a second concentration peak at approximately 8 h. This formulation allows for a rapid onset of effect by 1 h and a duration of action through 12 h after dosing. The chemistry, PK, efficacy and adverse event profile of MPH-MLR will be reviewed. Expert commentary : Although the PK profile may prove beneficial to patients in the late afternoon and early evening, it is not clear if this is a significant advantage compared with other MPH-ER formulations.